Effect of Holding Time and Cooling Media on Heat Treatment Process to Gear Motor Indopart Hardness. Issue 1 (May 2021) - Rahangmetan, Klemens A.; Cipto,; Wullur, Christian W.; Parenden, D; Sariman, Farid
Abstract: Industrial and technological advancements are growing rapidly, closely related to various machine tools, including the metal and construction industries. In the field of machinery many metal elements such as steel are involved. The progress of the metal industry has an important role, especially in the automotive world which uses a lot of metal materials. Therefore an attempt arises to change its mechanical properties in order to change the level of violence. This study aims to determine the level of medium carbon steel hardness (indopart gear motor), and determine the interaction between the two variables and determine the most optimal level of hardness. The method used in this study is the method of observation and literature on the fundamental theories, the sample used in this study is medium carbon steel (indopart gear motor) which is heat treated with a holding time of 60 minutes, 120 minutes and 180 minutes and with water, oil, diesel and air cooling media. Then hardness testing is done. Based on the results of the analysis of the data obtained there is a significant difference in the effect of the average cooling media on the level of violence, there is no significant difference in the effect on the average hardness between the holding time, there is a difference in the effect of the interaction between the holding time and the cooling media. The optimal treatment process is where the holding time is for 180 minutes using water media.